2021
DOI: 10.3389/falgy.2021.780425
|View full text |Cite
|
Sign up to set email alerts
|

TLR Signals in Epithelial Cells in the Nasal Cavity and Paranasal Sinuses

Abstract: The respiratory tract is constantly at risk of invasion by microorganisms such as bacteria, viruses, and fungi. In particular, the mucosal epithelium of the nasal cavity and paranasal sinuses is at the very forefront of the battles between the host and the invading pathogens. Recent studies have revealed that the epithelium not only constitutes a physical barrier but also takes an essential role in the activation of the immune system. One of the mechanisms equipped in the epithelium to fight against microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…The nasal epithelium expresses all known TLRs. 224 Variations in the 10 TLR genes have been associated with AR in several candidate gene studies and three large GWASs. A significant excess of rare variants in rhinitis patients was detected in TLR1, TLR5, TLR7, TLR9, and TLR10 225 but not in TLR8.…”
Section: Allergic Rhinitis Alone: Local Disease Associated With Tlr S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nasal epithelium expresses all known TLRs. 224 Variations in the 10 TLR genes have been associated with AR in several candidate gene studies and three large GWASs. A significant excess of rare variants in rhinitis patients was detected in TLR1, TLR5, TLR7, TLR9, and TLR10 225 but not in TLR8.…”
Section: Allergic Rhinitis Alone: Local Disease Associated With Tlr S...mentioning
confidence: 99%
“…The nasal epithelium expresses all known TLRs 224 . Variations in the 10 TLR genes have been associated with AR in several candidate gene studies and three large GWASs.…”
Section: “One‐airway‐one‐disease” Disentangled Refined and Beyondmentioning
confidence: 99%
“…Though precise lineage tracing study has shown the origin of fibroblasts in healthy or injured tissues, the origins and specific activation processes of CAFs are still lacking (6,7). Several cells may be predecessors of CAFs, such as normal fibroblasts (8), mesenchymal stem cells (MSCs) (9), pancreatic stellate cells (PSCs) (10), epithelial cells (11), endothelial cells (12), adipocytes (13), pericytes (14), hematopoietic stem cells (15) and cancer stem cells (CSCs) (16). The changes in the microenvironment where these precursor cells exist in may be a primary inducer of CAF transition (3).…”
Section: The Origin and Transition Of Cafsmentioning
confidence: 99%
“…Epithelial or endothelial cells are found to be the probable origins of CAFs through epithelial-tomesenchymal transition (EMT) or endothelial-to-mesenchymal transition (EndMT). The human nasal epithelial cells were activated and displayed CAF phenotypes such as FSP or FAP through EMT when they were exposed to matrix metalloproteinase (MMP)-9 (11). TGF-b could induce proliferating endothelial cells into fibroblast-like cells (12).…”
Section: The Origin and Transition Of Cafsmentioning
confidence: 99%
“…Primary human nasal epithelial cells (HNECs) were taken from the nasal mucosa of donors in a method as previously described (15)(16)(17). The cells were suspended in Bronchial Epithelial Growth Medium (BEGM, CC-3170, Lonza, Walkersville, MD, USA), supplemented with 2% Ultroser G (Pall Corporation, Port Washington, NY, USA).…”
Section: Primary Human Nasal Epithelial Cell Culturesmentioning
confidence: 99%